Gelling Power Alteration on Kappa-Carrageenan Dispersion through Esterification Method with Different Fatty Acid Saturation - Yoga W. Wardhana; Nuur Aanisah; Iyan Sopyan; Rini Hendriani; Anis Y. Chaerunisaa (Gels, 2022)
The physicochemical properties of κ-carrageenan gels and their ester forms derived from different fatty-acid saturations were characterized and compared with those of native κ-carrageenan. Furthermore, stearic and oleic acids were used as the saturated and unsaturated fatty acids, respectively. Fourier-transform infrared (FTIR) spectra confirmed the introduction of the ester into the κ-carrageenan backbone. The thermogravimetric analysis showed that thermal stability increased along with the level of unsaturation, but there was a decrease in viscosity, hardness, and syneresis, which caused the consistency of the product to become more elastic. The results also showed that the ester form still has a swelling ability that is almost the same as that of κ-carrageenan. After being formulated into a gel dosage form, the product was successfully produced from the ester with unsaturated fatty acids, and it was more elastic than native κ-carrageenan and had good physical properties with spreadability that meets the requirements for topical preparations.